Contemporary Greek horror cinema: Yes! It is a ‘Thing’! - Fotiou, Mikela (Journal of Greek Media & Culture, 2016)
Abstract Although horror films are quite prevalent in Hollywood as well as in various national cinemas, they are not so in the tradition of Greek cinema. However, there are several Greek horror films as well as film-makers – both amateur and professional – working on the genre. This article provides an overview of contemporary horror cinema in Greece, briefly discussing its background and highlighting a change both in the quantity and quality of Greek horror films after 2010. The article also presents key themes found in Greek horror films and traces threads that connect the films while also noting the ways recent horror films have been influenced by and commented upon the Greek economic and sociopolitical crisis. It situates these films in an emerging culture that surrounds, sustains, and seeks to develop this phenomenon in Greece. Finally, the article is followed by an appendix that offers a chronologically organized indicative list of Greek horror films encountered online during this research from early precursors in the mid-1970s to the more recent production discussed in the article, from 2004 down to the present.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qZ21jLjIuMi4yMTdfMQ